Effect of Adventitial Dissection in Brachiobasilic Arteriovenous Fistulae Opened in Children as Vascular Access for Hemodialysis on Patency and Maturation of Fistulae. (1st July 2004) - Karabay, Ozalp; Bak, Mustafa; Silistreli, Erdem; Calkavur, Sebnem; Yurekli, Ismail; Agin, Hasan; Acikel, Unal
Abstract : Background: Recently, therapy of pediatric patients with chronic renal failure has been carried out using hemodialysis, peritoneal dialysis, or renal transplant. In this study, we prospectively investigated the role of adventitial dissection (performed on brachiobasilic arteriovenous fistulae in the antecubital area) in the patency rate, maturation, and early initiation of dialysis among pediatric cases undergoing chronic hemodialysis. Methods: Thirty children (7 male and 23 females) were included in this study. They were operated on at the Department of Cardiovascular Surgery of Alsancak State Hospital and Dokuz Eylul University between March 2001 and June 2003. Their mean age was 12.3 ± 2.9 years (range 7-17 years), and their mean weight was 25.5 ± 7.9 kg (range 16-44 kg). Children who underwent only brachiobasilic arteriovenous fistula operation were included. Group 1 ( n = 15) consisted of those who underwent adventitial dissection, and group 2 ( n = 15) consisted of those not receiving the adventitial dissection procedure. Results: The procedure was conducted by the same surgeon, and follow-up examinations were done at the Department of Pediatric Nephrology by investigators masked to treatment groups. Conclusion: There were no significant differences in age, sex, existence of preoperative hypertension, diameter of vein measured preoperatively, and first day of dialysis between the groups. In 29 cases, a palpable thrill was noted at the operation site. Hemodialysis had been initiated after the fourth week, when the fistulae had matured. The mean duration of follow-up was 12.53 ± 8.98 months in group 1 and 11.85 ± 7.55 months in group 2 ( p = .880). In group 1, one case developed fistula infection in the second month and one case developed lymphatic drainage. In group 2, one case developed early thrombosis, one case developed hematoma, and one case developed transient ischemia owing to arterial spasm in the ipsilateral limb. One case in each group developed minimal edema in the forearm, which was treated conservatively. The primary patency rate was 93.3% in both groups, whereas the secondary patency rate was 100% in group 1. Adventitial dissection performed on the vein during arteriovenous fistula formation does not result in any additional benefit with respect to fistula maturation, early initiation of dialysis, and patency. Among pediatric patients with chronic renal failure, in cases of inappropriate forearm veins, brachial arteriovenous fistulae performed with a meticulous surgical technique should be the procedure of choice because it is associated with minimal complications and a high patency rate.